UNIT 29.7 Methods for Studying Interactions of Detergents and Lipids with α‐Helical and β‐Barrel Integral Membrane Proteins. Issue 1 (5th November 2013) - Saif Hasan, S.; Baniulis, Danas; Yamashita, Eiki; Zhalnina, Mariya V.; Zakharov, Stanislav D.; Stofleth, Jason T.; Cramer, William A.
Abstract: Methods for studying interactions of protein with lipids and detergents are described for representatives of two major classes of membrane proteins: (1) the α‐helical hetero‐oligomeric integral cytochrome b 6 f complex of oxygenic photosynthesis from cyanobacteria, and (2) the outer membrane β‐barrel proteins BtuB and OmpF from Gram‐negative Escherichia coli bacteria. Details are presented on the use of detergents for purification and crystallization of the b 6 f complex as well as a method for lipid exchange. The positions of detergent and lipid molecules, which define eight potential lipid‐binding sites in the b 6 f complex, are described. Differences in detergent strategies for isolation and crystallization of β‐barrel proteins relative to those for oligomeric helical membrane proteins are discussed, and purification and assessment of protein quality by circular dichroism (CD) is presented. Curr. Protoc. Protein Sci . 74:29.7.1‐29.7.30. © 2013 by John Wiley & Sons, Inc.